1999
DOI: 10.1159/000024187
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Intercellular Adhesion Molecule–1 in Sera of Children with Bronchial Asthma Exacerbation

Abstract: Previous studies have suggested that intercellular adhesion molecule–1 (ICAM–1; CD54) may be involved in the pathogenesis of asthma. In addition, a soluble form of intercellular adhesion molecule–1 (sICAM–1) has been detected in increased concentrations in the sera from adult patients with certain inflammatory, immune, or malignant diseases. To determine whether bronchial asthma exacerbation in children is associated with increased levels of serum sICAM–1 and to investigate the effect of the severity of exacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 21 publications
(40 reference statements)
0
7
1
Order By: Relevance
“…Intercellular adhesion molecule‐1 is essential for leucocyte recruitment into the inflammatory focus but the meaning of its detection in biological fluids is not clear. The increase in serum ICAM‐1 levels observed in the treated group at the end of the study might suggest an anti‐inflammatory role for this molecule by blocking the endothelial receptor for ICAM‐1 [34]. In our study, ICAM‐1 values were not modified by the Dpt‐BPT at either T0 or T12, which is in contrast to other authors [35].…”
Section: Discussioncontrasting
confidence: 86%
“…Intercellular adhesion molecule‐1 is essential for leucocyte recruitment into the inflammatory focus but the meaning of its detection in biological fluids is not clear. The increase in serum ICAM‐1 levels observed in the treated group at the end of the study might suggest an anti‐inflammatory role for this molecule by blocking the endothelial receptor for ICAM‐1 [34]. In our study, ICAM‐1 values were not modified by the Dpt‐BPT at either T0 or T12, which is in contrast to other authors [35].…”
Section: Discussioncontrasting
confidence: 86%
“…23 It has been reported that increased soluble selectins could be a promising serological marker of the severity of inflammation in bronchial asthmatic children. 24 The present study suggests that elevated levels of these molecules may reflect the inflammatory process in asthmatic adults. Because attachment of circulating cells to endothelium is a key event in their recruitment to the inflammatory sites, the association of higher concentrations of soluble selectins with severe asthma suggests that E-selectin and VCAM-1 are involved in the inflammatory pathways of this kind of asthma.…”
Section: Discussionmentioning
confidence: 54%
“…Similar concentrations of sICAM‐1 in atopic and non‐atopic children were found, indicating that sICAM‐1 is not associated with atopy. One previous study showed no difference in sICAM‐1 levels between healthy and asthmatic children (independent of atopy) [32], but other workers found elevated concentrations of sICAM‐1 in asthmatic children compared to non‐asthmatic controls, both when the disease was stable and during an exacerbation [33, 34]. It has been suggested that sICAM‐1 may block cell–cell interactions, hampering inflammatory responses [35].…”
Section: Discussionmentioning
confidence: 99%